Mussel watch in Malaysia : past, present and future - Yap, Chee Kong (Universiti Putra Malaysia Press, 2012)
This book reviews the major aspects of ecology and ecotoxicology of Perna viridis around the Asia-Pacific coastal waters especially in Malaysia with special reference to heavy metals. This book provides a good start for biomonitoring heavy metal pollution in Malaysia by implementing the Mussel watch approach which is cost effective and widely recognized worldwide. The author has published more than 60 refereed papers on P. viridis in Malaysia from studies carried out from 1998 until 2007 and thus justifiably able to compile the relevant information to write this book on Mussel watch in Malaysia. He has arranged the list of contents by focusing on the criteria for a good biomonitor which mostly fulfilled. Past, present and future prospects of research opportunities related to this species are also discussed in this book.